ПОРІВНЯЛЬНИЙ АНАЛІЗ ЮРИДИЧНИХ ФАКТІВ ЯК ПІДСТАВИ ВИНИКНЕННЯ ПОДАТКОВИХ ПРАВOВIДНOСИН - Хатнюк, Наталія Сергіївна (SUPREMANCE OF LAW, 2016)
In the sdentîfic article an аиїНог pays regard to research оф essence оф nature оф legalfacts as as a fundamental оф legal category оф tax law, analyses the general and spedal signs оф legal facts, whtoh cause motion оф tax legal relationships, exposes the doctrinegoingnear the dedston оф wnceptоф legalфacts іп the different areas oфlegal sdence and the campattble dedston оф wncept oфlegalфacts asgreunds офedgm оф tax legal relattonsfaps effers, that positively will mfluence оп a іїєогу and practice оф them legal adjusting іп Ukrame.
Keywords: legafjacts; general and spedal signs офlegalpacts; фoundation oфorigin оф tax legal relationships; legal pacts; asфoundation oфorigin оф tax legal relationships.